Thermoplastic Elastomers of Polystyrene-Based Reinforced with Natural Rubber and Carbon Filler from Oil Palm Empty Fruit Bunches - Indah Agus Setiorini; Achmad Faisal Faputri; Rahma Nuryanti; Amiliza Miarti; Muhammad Rasyad Hilmi; Hasrinah Hasbullah (CHEESA: Chemical Engineering Research Articles, 2026)
Polystyrene (PS) has limited resistance to extreme temperatures, often becoming soft, brittle, and losing its elasticity. To address these limitations, the material was modified by adding Natural Rubber (NR) and oil palm empty fruit bunch (OPEFB) carbon filler. Therefore, this research aimed to modify the surface of PS by adding NR and OPEFB carbon filler, followed by analysis of the resulting morphology, thermal stability, and enthalpy change (ΔH) of the composites. The polystyrene grafting with maleic anhydride (PS-g-MA) was carried out at 75 °C for 10 minutes. The composition variations of PS-g-MA/NR/OPEFB carbon filler were (30:65:5) wt%, (30:60:10) wt%, (30:55:15) wt%, (30:50:20) wt%, and (30:45:25) wt%. The highest thermal stability (T5%) was achieved with 10% filler at 363°C. However, morphological analysis showed that increasing the filler content to 20% provides an optimal point in balancing interfacial interaction (maximum adhesion) and phase dispersion, with a ΔH value of -27.86 J/g.